PERAN FORUM SILATURAHMI REMAJA ISLAM (FOSRI) DALAM MENINGKATKAN SPIRITUAL WARGA KELURAHAN BOLONG - Yunita Ashari; Triono Ali Mustofa (PAI RAFAH, 2023)
The purpose of this study is to describe the role of the Islamic Youth Gathering Forum in improving the spirituality of residents in Bolong Village and to find out the results and impacts of the Islamic Youth Gathering Forum activities in Bolong Village. The data collection techniques used were participant observation, interviews, and documentation, where residents and the Islamic Youth Gathering Forum (FOSRI) became the research subjects. The research results include: The role of FOSRI takes the form of implementing various kinds of religious activities like activity preaching, activities taklim, and social religious activities. Activity preaching covers studies, festivals Islamic boarding school students, and Tahrib Ramadhan. Activity ta’lim held with form Study reciting the Qur’an, and tahsin, meanwhile social religious activities form compensation together child orphan, Ramadhan with FOSRI, fundraising, and activities outside That like celebration day big Islam. Results or the impact obtained by residents in the Village Hole is own interests, talents, and achievements achieved related to religion, attitudes, and behavior shown by citizens reflect morals karimah, capable control social relations, prosperous mosques, abundance TPQ students, close ukuwah Islamiyah inter residents in the Village Holes and creation environment Islamic society.